Experimental and numerical study of hot-rolled duplex stainless steel CHS columns. (May 2021) - Ning, Keyang; Yang, Lu; Wang, Jie; Dai, Peng; Sun, Yinan
Abstract: Stainless steel circular hollow section (CHS) members have been widely used in building structures because of their comparable strength to structural carbon steels, attractive appearance and excellent corrosion resistance. However, research on stainless steel CHS members has been limited to cold-formed members, whereas hot-rolled CHS columns have received less attention. To this end, the flexural buckling performance of hot-rolled duplex stainless steel CHS columns was investigated by a comprehensive experimental and numerical programme. A total of seven hot-rolled duplex stainless steel CHS columns covering two cross-sectional sizes with varying lengths have been tested under compression. Based on the test results, finite element (FE) models were developed and used in parametric studies to generate data points with a wider range of geometric dimensions. Comparing the test and FE results with current design guidance, it was found that the Chinese standard, CECS 410, and North American design guidance, AISC DG 27, underestimate significantly the flexural buckling resistance of such columns, while the design method in Eurocode 3: Part 1–4 might be unsafe in predicting the resistances for low slenderness values. New column buckling curves based on the Eurocode 3 and AISC DG 27 design formulae with improved accuracy and reduced scatters were also proposed and validated through careful reliability analysis. Graphical abstract: Unlabelled Image Highlights: Seven hot-rolled duplex stainless steel CHS columns were tested. The developed FE models were validated and employed for parametric studies. Based on the test and FE results, three design methods were assessed. New column buckling curves were proposed to give more accurate predictions.